Konsep Ahimsa Menurut Mahatma Gandhi dan Relevansinya Dalam Komunikasi Manusia Masa Kini: Sebuah Kajian Filsafat - Delviano Gregorius Kapele; Barnabas Ohoiwutun (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2023)
Mahatma Gandhi was a human rights activist from India. Born into a devoted Hindu family, Gandhi believed in ahimsa. Gandhi made ahimsa as a way of life to find the Truth. Current conditions and the thoughts of several figures such as Leo Tolstoy, John Ruskin, and Henry Thoreau helped reinforce Gandhi’s thoughts on ahimsa. Gandhi declared ahimsa to be a spiritual force that surpasses all forces in the world. Gandhi gave a new deeper meaning to ahimsa. Ahimsa was understood as a method of struggle against various practices of violence and injustice in order to gain the truth. Starting from Gandhi’s understanding of ahimsa, it is very relevant if the concept of ahimsa is used in contemporary human communication to prevent and resolve conflicts. The various challenges that confront the practice of ahimsa can be overcome when people turn their backs to himsa and practice ahimsa. Using descriptive and analysis method, this essay attempts to explain Mahatma Gandhi’s concept of ahimsa and its relevance in human communication today.